Gefitinib provides similar effectiveness and improved safety than erlotinib for advanced non-small cell lung cancer: A meta-analysis. Issue 16 (April 2018) - Zhang, Wenxiong; Wei, Yiping; Yu, Dongliang; Xu, Jianjun; Peng, Jinhua
Abstract: Background: The epidermal growth factor receptor tyrosine kinase inhibitors gefitinib and erlotinib are effective for advanced non-small cell lung cancer (NSCLC). This meta-analysis compared their effectiveness and safety. Methods: We searched systematically in PubMed, ScienceDirect, The Cochrane Library, Scopus, Ovid MEDLINE, EMBASE, Web of Science, and Google Scholar for relevant clinical trials regarding gefitinib versus erlotinib for NSCLC. Antitumor effectiveness (overall survival [OS], progression-free survival [PFS], objective response rate [ORR] and disease control rate [DCR]) and adverse effects [AEs]) were assessed. Results: Forty studies comprising 9376 participants were included. The results suggested that gefitinib and erlotinib are effective for advanced NSCLC with comparable PFS (95% confidence intervals [CI]: 0.98–1.11, P =  .15), OS (95% CI: 0.93–1.19, P =  .45), ORR (95% CI: 0.99–1.16, P =  .07), and DCR (95% CI: 0.92–1.03, P =  .35). For erlotinib, dose reduction was significantly more frequent (95% CI: 0.10–0.57, P =  .001) as were grade 3 to 5 AEs (95% CI: 0.36–0.79, P =  .002). In the subgroup analysis, the erlotinib group had a significant higher rate and severity of skin rash, nausea/vomiting, fatigue, and stomatitis. Conclusions: Gefitinib was proven to be the better choice for advanced NSCLC, with equal antitumor effectiveness and fewer AEs compared with erlotinib. Further large-scale, well-designed randomized controlled trials are warranted to confirm our validation. Abstract : Supplemental Digital Content is available in the text